Active Multisensory Learning with Somatic Auditory Visual Intellectual Model and Alphabet Cards for Early Reading: Pembelajaran Multisensori Aktif dengan Model Somatik Auditori Visual Intelektual dan Kartu Alfabet untuk Membaca Permulaan - Selviola; Aprizan; Habibie, Zulqoid R (Indonesian Journal of Innovation Studies, 2025)
Background: Early reading is a foundational literacy skill that supports all subsequent learning. Specific background: Many early grade students struggle with recognizing letters, reading syllables, and forming words, which delays literacy development. Knowledge gap: Previous studies often examined either the SAVI model or visual media separately, but few integrated both approaches in a multisensory framework for early reading. Aim: This study aimed to optimize early reading learning by applying the SAVI (Somatic, Auditory, Visual, Intellectual) model supported by Alphabet Cards for grade 2 students. Results: Using a classroom action research design over two cycles, teacher performance improved from 75% (good) to 90% (very good), student activity rose from 70.8% to 87.5%, and reading mastery increased from 62.5% to 83.3%, surpassing the 80% mastery threshold. Novelty: This research explicitly integrates a multisensory SAVI approach with alphabet media, offering a more engaging and holistic reading experience. Implications: The findings suggest that multisensory, interactive strategies can strengthen student motivation, support literacy acquisition, and improve teaching practice in early primary classrooms. Highlights Teacher performance improved significantly between the first and second cycle. Student participation and confidence increased through multisensory activities. Reading mastery exceeded the minimum classical mastery threshold. Keywords Early Reading Skills, SAVI Model, Alphabet Cards, Multisensory Learning, Primary Education